Adopting the Standard of Financial Instruments IFRS9 and its Impact on the Quality of Financial Reporting - Saja Akram Abdul Razzaq Al-Sheikhly,; Abbas Yahya Hamid Tamimi, (International Journal of Psychosocial Rehabilitation, 2020)
The adoption of standards has become a must in light of the developments and mergers that have taken place in the economic units, and therefore it is not reasonable for Iraq to remain isolated from the outside world, especially after it became open to it and its interests became intertwined with many countries of the world, this necessitates the adoption of international accounting and financial reporting standards, and the importance of financial instruments and derivatives for many economic units. IFRS 9 requires the economic units that will adopt adjustments to their accounting systems and records, as well as the reclassification of their financial instruments as well as the preparation and training of their accounting staff, all of which pose challenges for the economic units seeking to adopt this standard. The adoption of this standard can be reflected in the quality of financial reporting of these units and their suitability, credibility and accuracy, financial reports are responsible for the delivery of financial and non financial information that influences the decision-making process of the beneficiaries of these financial statements and the impact on the economic activity of those units